2008
DOI: 10.1134/s0006297908050118
|View full text |Cite
|
Sign up to set email alerts
|

Transport proteins of the ABC family and multidrug resistance of tumor cells

Abstract: Some new data concerning the role of transport proteins of the ABC family in multidrug resistance (MDR) of human tumor cells, and problems connected with regulation of these proteins are considered. MDR is a complex phenomenon that may be caused simultaneously by several mechanisms functioning in one and the same cell. Among them there may be the alterations of activity of several transport proteins. Activation of these proteins may be associated with alterations of activities of different cell protective syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
11

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 74 publications
0
98
0
11
Order By: Relevance
“…41 Hypoxia induces cellular adaptations which contribute to cancer progression and chemoresistance, with one of these adaptations being the expression of multidrug resistance proteins such as ABC transporters. 42 Evidence of MDR-1 or MRP1 upregulation through HIF-1 under hypoxia has recently been highlighted. 43,44 In the present study, we observed increased chemosensitivity to THP in HIF-1a shRNA-treated cells, compared with NC shRNA treated or untreated cells, supporting the notion that the combination of gene therapy and chemotherapy may be a new hope for TNBC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…41 Hypoxia induces cellular adaptations which contribute to cancer progression and chemoresistance, with one of these adaptations being the expression of multidrug resistance proteins such as ABC transporters. 42 Evidence of MDR-1 or MRP1 upregulation through HIF-1 under hypoxia has recently been highlighted. 43,44 In the present study, we observed increased chemosensitivity to THP in HIF-1a shRNA-treated cells, compared with NC shRNA treated or untreated cells, supporting the notion that the combination of gene therapy and chemotherapy may be a new hope for TNBC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a side population has been also reported in PCa cells (Pascal et al 2007). Interestingly, ABC transporters are thought to be responsible for drug resistance in most cancers (Sharom 2008;Stavrovskaya andStromskaya 2008), including PCa (Sánchez et al 2009;Sánchez et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that one of the most common mechanisms of cancer MDR is the over-expression of the efflux pumps 29 , which are membrane proteins that can recognise and extrude out of the cells toxic agents such as the anticancer drugs 29,30 . In this context, different studies 6,7,[14][15][16][31][32][33] pointed out that selenocompounds can enhance the activity of the drugs used in cancer chemotherapy in a synergic way if they are applied together.…”
mentioning
confidence: 99%